Synergetic Control of Grid-Connected Photovoltaic Systems - Junjie Qian; Kaiting Li; Huaren Wu; Jianfei Yang; Xiaohui Li (International Journal of Photoenergy)
It is important to improve the dynamic performance and the low-voltage ride-through (LVRT) capability of a grid-connected photovoltaic (PV) system. This paper presents synergetic control for the control of a grid-connected PV system. Modeling of a grid-connected PV system is described, and differential-algebra equations are obtained. Two control strategies are used in normal operation and during LVRT of a PV system. Practical synergetic controllers with two control strategies are synthesized. The mathematical expressions are derived for computing control variables. The design of the synergetic controllers does not require the linearization of the grid-connected PV system. A grid-connected PV system with synergetic controllers is simulated in Simulink surroundings. The control performance is studied in normal operation and during LVRT. Simulation results show that the synergetic controllers are robust and have good dynamic characteristics under different operation states.